Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2196/41288
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sleep Disorders From Search Engine Activity: Combining User-Generated Data With a Clinically Validated Questionnaire

Abstract: Background Sleep disorders are experienced by up to 40% of the population but their diagnosis is often delayed by the availability of specialists. Objective We propose the use of search engine activity in conjunction with a validated web-based sleep questionnaire to facilitate wide-scale screening of prevalent sleep disorders. Methods Search advertisements offering a web-based sleep disorder screening questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…22,25 A wide range of conditions of interest was examined. Broadly, included conditions encompassed mental health (i.e., schizophrenia spectrum disorder, suicidality, mood disorders, psychosis, eating disorders), 19,22,24,[26][27][28][29][30] neurologic conditions (i.e., Parkinson's disease, amyotrophic lateral sclerosis, stroke, sleeping disorders), [31][32][33][34] malignancies (i.e., pancreatic cancer, lung cancer, paediatric oncology, breast cancer, colon cancer, gynaecological malignancies), 23,25,[35][36][37] miscellaneous conditions (i.e., diabetes, coeliac disease, biliary atresia, pyloric stenosis), 20,21,38,39 and a variety of primary and secondary care presentations. 40,41 Ten studies recruited participants from inpatient or outpatient settings, and consented participants face-to-face.…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…22,25 A wide range of conditions of interest was examined. Broadly, included conditions encompassed mental health (i.e., schizophrenia spectrum disorder, suicidality, mood disorders, psychosis, eating disorders), 19,22,24,[26][27][28][29][30] neurologic conditions (i.e., Parkinson's disease, amyotrophic lateral sclerosis, stroke, sleeping disorders), [31][32][33][34] malignancies (i.e., pancreatic cancer, lung cancer, paediatric oncology, breast cancer, colon cancer, gynaecological malignancies), 23,25,[35][36][37] miscellaneous conditions (i.e., diabetes, coeliac disease, biliary atresia, pyloric stenosis), 20,21,38,39 and a variety of primary and secondary care presentations. 40,41 Ten studies recruited participants from inpatient or outpatient settings, and consented participants face-to-face.…”
Section: Study Participantsmentioning
confidence: 99%
“…22,28,34 Two studies recruited participants with targeted advertisements on search engines. 33,37 Nine studies extracted search data from unique, non-identi able users from back-end databases (8 Bing, 1…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tkachenko et al [ 30 ] revealed that Google Trends could detect early signs of diabetes by monitoring combinations of keywords in online search queries. Sleep disorders [ 31 ] and mental health problems [ 32 ] were also found to be related to search volumes.…”
Section: Introductionmentioning
confidence: 99%